(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article explains the importance of increasing the employment level of the population of the region as a result of the development of tourism in the Namangan region, further increasing the standard of living of the population, increasing the level of GDP, further benefiting from tourist opportunities. In this regard, work has been done so far, proposals have been considered. As a result of working with statistical data, proposals were made for problems in the development of the industry.